2017
DOI: 10.1002/jpln.201700013
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide enhances selenium concentration by promoting selenite uptake by rice roots

Abstract: Nitric oxide (NO) plays a key role in regulating a wide range of physiological and biochemical processes. This study investigated possible effects of NO, which was supplied by sodium nitroprusside (SNP), NO donor, on selenium (Se) concentration, Se species within roots, activities and gene transcription of selenite uptake, and metabolism‐related transporters or enzymes using ICP‐MS, HPLC‐ICP/MS, qRT‐PCR, fluorescence imaging, and biochemical analysis in the roots of rice (Oryza sativa L.) seedling. A suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…1, 2, and 4b). In line with the previous assumptions [27, 28], the unique expression patterns presenting in the two rice varieties support that OsNIP2;1 may serve as a main positive regulator in Se transportation. Although the result showed that Se continuously induces the expression of OsSultr1;2 , a sulfate transporter in presence of all concentrations of Se, we observed no obvious difference between the two rice varieties in those scenarios (Fig.…”
Section: Resultssupporting
confidence: 88%
“…1, 2, and 4b). In line with the previous assumptions [27, 28], the unique expression patterns presenting in the two rice varieties support that OsNIP2;1 may serve as a main positive regulator in Se transportation. Although the result showed that Se continuously induces the expression of OsSultr1;2 , a sulfate transporter in presence of all concentrations of Se, we observed no obvious difference between the two rice varieties in those scenarios (Fig.…”
Section: Resultssupporting
confidence: 88%
“…1, 2, and 4b). In line with the previous assumptions [37,38], the unique expression patterns presenting in the two rice varieties support that OsNIP2;1 may serve as a main positive regulator in Se transportation. Although the result showed that Se continuously induces the expression of OsSultr1;2, a sulfate transporter in presence of all concentrations of Se, we observed no obvious difference between the two rice varieties in those scenarios (Fig.…”
Section: The Gene Expression Patterns Of Se Uptake-and Transport-relasupporting
confidence: 88%
“…Furthermore, NO supplementation stimulated glutathione biosynthesis by up-regulating γglutamylcysteine synthetase (γ-ECS) and glutathione synthetase (GS), and increased the expression of cysteine synthase (CS) resulting in triggered Se metabolism. These data imply the possibility that not only selenium affects endogenous NO/RNS metabolism and signaling, but also that NO has an effect on Se uptake and metabolism (Xiao et al, 2017).…”
Section: A C C E P T E Dmentioning
confidence: 73%